2012
DOI: 10.1016/j.athoracsur.2011.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury Increases Mortality After Lung Transplantation

Abstract: Background Acute kidney injury requiring renal replacement therapy (RRT) is associated with increased mortality after cardiac surgery. Studies examining the impact of RRT after lung transplantation (LTx) are limited. We evaluated risk factors and outcomes associated with RRT after LTx. Methods We retrospectively reviewed all LTx recipients in the United Network for Organ Sharing database. Preoperative renal function was stratified by glomerular filtration rate (GFR) as determined by the Modification of Diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
58
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 27 publications
14
58
3
Order By: Relevance
“…The prevalence of AKI and RRT in our data were higher than in previous reports (41.2% and 16.2%, respectively), the finding in our study that the need for RRT after lung transplantation increased mortality was similar to previous reports (29,30). Several studies have shown the reasons for the high risk of AKI in recipients of lung transplantation; for example, lung injury could induce inflammatory mediators of the renal epithelium, nephrotoxic agents including calcineurin inhibitors could induce direct injury, and efforts to maintain negative balance might cause kidney injury after transplantation.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The prevalence of AKI and RRT in our data were higher than in previous reports (41.2% and 16.2%, respectively), the finding in our study that the need for RRT after lung transplantation increased mortality was similar to previous reports (29,30). Several studies have shown the reasons for the high risk of AKI in recipients of lung transplantation; for example, lung injury could induce inflammatory mediators of the renal epithelium, nephrotoxic agents including calcineurin inhibitors could induce direct injury, and efforts to maintain negative balance might cause kidney injury after transplantation.…”
Section: Discussioncontrasting
confidence: 56%
“…AKI after lung transplantation developed in 37%, and the incidence of RRT was 5.51% in some previous studies (29,30). The prevalence of AKI and RRT in our data were higher than in previous reports (41.2% and 16.2%, respectively), the finding in our study that the need for RRT after lung transplantation increased mortality was similar to previous reports (29,30).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…12 In this study, 8 patients (8%) needed postoperative renal replacement therapy, which is higher than what has been reported earlier. 12 This finding might be due to the small number of patients included. Another explanation could be the different triggers to start renal replacement therapy in different centers.…”
Section: Discussioncontrasting
confidence: 57%
“…7,11,[13][14][15] Renal failure continues to be one of the most devastating complications of transplantation, occurring partially as a result of the toxicity profile of immunosuppression therapy. 15 Advancing age is associated with diminished renal function, but, interestingly, we observed no differences in risk of renal failure requiring dialysis between the two groups in either uni-or multivariate analyses. Our results also show that age had no bearing on the risk of rejection at 1 year or on overall hospital LOS.…”
Section: Discussionmentioning
confidence: 99%